Influence of Alveolar Bone Loss and Cement Layer Thickness on the Biomechanical Behavior of Endodontically Treated Maxillary Incisors: A 3-dimensional Finite Element Analysis - Dal Piva, Amanda Maria de Oliveira [UNESP]; Tribst, João Paulo Mendes [UNESP]; Souza, Rodrigo Othávio de Assunção e; Borges, Alexandre Luiz Souto [UNESP] (Elsevier, 2017)
Introduction In order to understand the mechanical behavior of a weakened incisor, this study aimed to evaluate the stress distribution caused by different alveolar bone heights and cement layer thickness. Methods A finite element analysis was conducted for this investigation. An intact maxillary central incisor was initially modeled, and the bone of the models was modified in order to simulate 4 levels of bone height: BL0 (no bone loss), BL1 (1/3 bone loss), BL2 (1/2 bone loss), and BL3 (2/3 bone loss). These teeth models were remodeled with a fiber post at 2 different cement thicknesses and restored with a ceramic crown; “A” refers to the well-adapted fiber post (0.3 mm) and “B” to the nonadapted fiber post (1 mm), resulting in 12 models. RelyX ARC (3M ESPE, St Paul, MN) cement was simulated for the cementation of the crowns and fiber posts for all groups. Numeric models received a load of 100 N on the lingual surface. All materials and structures were considered linear elastic, homogeneous, and isotropic. Numeric models were plotted and meshed with isoparametric elements, and results were expressed in maximum principal stress. Results For fiberglass posts, cement, and dentin, the highest stress concentration occurred in the groups with increased bone loss. For cortical bone, the highest values were for the groups with 1/3 bone loss. A greater thickness of cement layer concentrates more stress. Conclusions More bone loss and greater CLT were the influential factors in concentrating the stress.
Keywords: Alveolar bone loss; dental prosthesis; finite element analysis; post and core technique